(untitled) - Khanna, Prem Nath (New Delhi, 1997)
The object this volume is to give a fairly complete but concise account of the various subjects to serve as a ready reference for everyday-work problems which constantly co-front the engineers,...
Keywords: Civil engineering,Công nghệ xây dựng; Handbooks, manuals, etc,Sách hướng dẫn